(untitled) - 1968-; Monaghan, Dominic; 1976-; Bloom, Orlando; 1977-; Lesnie, Andrew; 1956-2015.; Selkirk, Jamie; Shore, Howard; Dickson, Ngila; Tolkien, J. R. R.; (John Ronald Reuel); et al. (Distributed by Warner Home Video, 2003)
Frodo makes his way through the darkness to Mount Doom to destroy the One Ring. Aragon learns of his destiny as the true King and the others prepare for a massive battle that will determine the fate of Middle-Earth.
Keywords: Drama; Baggins, Frodo; Middle Earth (Imaginary place); Drama; Drama; Video recordings for the hearing impaired; Feature films